Extreme value analysis of rainfall in Myanmar (1970-2008) - Thet Htar Su Hlaing (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2010)
Extreme values of rainfall in Myanmar were analyzed using the daily observations from 1970 to 2008 (39 years ) of 35 synoptic weather stations. For each station and each year, the maximum 1-day, 2-day and 3-day rainfall were selected. When the maximum 1-day rainfall for each year was used, results show that extreme events most often occur during the southwest monsoon moths of May to September and contribute 95 % to the annual frequency of extreme rainfall and more extreme rainfall events happen after 2000 that the previous years.